The Use of Multistate Models to Examine Associations of Stress and Adherence With Transitions Among HIV Care States Observed in a Clinical HIV Cohort. (1st November 2017) - Blitz, Sandra; Antoniou, Tony; Burchell, Ann; Walmsley, Sharon; Light, Lucia; Gardner, Sandra; Rourke, Sean; Cooper, Curtis; Kendall, Claire; Loutfy, Mona; Rachlis, Anita; Wobeser, Wendy; et al.
Abstract : Background: The "cascade of care" is a framework for quantifying the trajectory of people with HIV along the continuum of HIV care. We extended this framework to recognize that individuals may transition back and forth between states of care and to identify factors associated with movement among states of care over time, with particular focus on stress, depression, and adherence. Methods: The Ontario HIV Treatment Network Cohort Study is a multisite HIV clinical cohort. We analyzed data from participants who had initiated antiretroviral therapy, achieved virologic suppression, completed ≥1 study questionnaire including psychosocial data, and had ≥1 viral load (VL) result within 2 years of a questionnaire. Follow-up time from the first suppressed VL was divided into 6-month intervals and classified into 1 of 3 states for HIV care retention: (1) suppressed VL (VL <50 copies/mL), (2) unsuppressed VL (VL >50 copies/mL), and (3) unobserved . Multistate models were used to determine the association of transitioning between states and time-updated demographic and clinical characteristics. Results: In total, 1842 participants were included. After multivariable adjustment, poor adherence [hazard ratio (HR) 1.88, 95% confidence interval (CI): 1.19 to 2.98) and stress (HR = 1.38; 95% CI: 1.04 to 1.83) were associated with transitions from suppressed to unsuppressed VL. Similarly, low adherence (HR = 1.52; 95% CI: 1.14 to 2.04) and stress (HR = 1.25; 95%: 1.03, 1.51) were associated with transitions from suppressed to unobserved states. Conclusions: Higher levels of stress and low adherence are associated with transitions to less favorable states of care. Interventions to manage stress and facilitate adherence may improve engagement in HIV care. Abstract : Supplemental Digital Content is Available in the Text.